Keputusan Investasi Perusahaan FCMG Saat Era Endemik Covid-19 Yang Dimoderasi Firm Performance - Merna Surjadi; Tandry Whittleliang Hakki; Christian Suryadi (Dinasti Review, 2024)
The investment process is a process when investors make decisions about the business or business sector to be chosen, how profitable it is if investors make investments, and when investments should be implemented to generate profits in the future. Investors who invest in stocks aim to maximize returns. This study aims to examine the Influence of Investment Decisions, Company Growth and Company Size on Stock Returns. Then the researcher also analyzed the role of firm performance as a moderation of the influence of Investment Decisions, Company Growth, and Company Size on stock returns. The type of data used in this study is secondary data in the form of financial reports of companies that are used as samples. The research method used in this study is a quantitative research method. The sample was selected using the purposive sampling method. For hypothesis testing, this study uses multiple linear regression analysis. Based on the results of this study, it shows that Investment Decisions have a significant effect on Stock Returns, Company Growth does not affect Stock Returns, Company Size has a significant effect on Stock Returns, Company Performance strengthens the influence of Investment Decisions on Stock Returns, Company Performance does not strengthen the influence of Company Growth on Stock Returns, Company Performance strengthens the influence of Company Growth on Stock Returns